KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT MUJI RAHAYU SURABAYA - Mei Indrawati (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
The purpose of this study was to analyze the satisfaction of outpatients at Muji Rahayu Hospital Surabaya in terms of the quality of services provided by Muji Rahayu Hospital Surabaya. This study uses independent variables consisting of tangibles, reliability, responsiveness, assurance and empathy. The analytical model used to test and prove the hypothesis in this study uses Multiple Linear Regression. Based on the results of regression analysis, the regression coefficients of all independent variables have a probability value (sig) less than 0.05, which means that partially tangibles, reliability, responsiveness, assurance and empathy have an effect on outpatient satisfaction at Muji Rahayu Hospital Surabaya is reliability. . The conclusion of this study is that tangibles, reliability, responsiveness, assurance and empathy both partially and simultaneously affect outpatient satisfaction at Muji Rahayu Hospital Surabaya and among tangibles, reliability, responsiveness, assurance and empathy, the dominant influence on outpatient satisfaction at Muji Rahayu Hospital Surabaya is reliability.